Crucial Contextual Theological Analysis Ma’nene’ Ritual In The View Bevans’ Anthropological Model - Benny Agustinus Triangga Prayitno; Hosianna Hosea (Jurnal Mamangan, 2024)
The discussion of Christian faith in the context of culture is a very crucial and interesting matter to be adjusted to the life of the church today. This adjustment is specifically seen in the context of the life of the Toraja people who are predominantly Christian, but are very strong in every cultural issue that is considered a fundamental thing in the life of the Toraja. The writing of this scientific work aims to bring readers to understand how the Ma'Nene' traditional ritual is based on the context of Torajan life seen in one of Bevans' models, namely the "anthropological" model. The interesting question of whether or not this ritual is true in the context of Torajan life is a question that feels quite ambiguous due to the various views that are relative according to the angle from which one sees it. In this case, an attempt to understand the relative truth in the Ma'Nene' Ritual is to see it from the perspective or glasses of the Bevans Anthropological model. Where, the departure point of this Anthropological model is experience, culture, social location and cultural changes that exist specifically seen in the context of the Kingdom.